The STEM Enhancement in Earth Science “Mosquito Mappers” Virtual Internship: Outcomes of Place-Based Engagement with Citizen Science - Cho, Holly; Low, Russanne D.; Fischer, Heather A.; Storksdieck, Martin (Frontiers in Environmental Science, 2021)
In this paper, we describe a virtual high school earth science enhancement program that embeds a citizen science experience within a scientist-mentored research internship. The STEM Enhancement in Earth Science (SEES) Mosquito Mappers Virtual Internship connected high school interns with research opportunities applying NASA Earth Observations to the global health threat of mosquito-vector borne diseases. The interns engaged in 120—150 hours of research working closely with NASA subject matter expert mentors, and making use of the GLOBE Observer citizen science infrastructure to collect and analyze data. Students completed a research project leveraging data collected using the place-based citizen science mobile application, GLOBE Observer. Participants were motivated by conducting fieldwork in and around their communities using the GLOBE Observer app. Local fieldwork enabled the student researchers to apply prior knowledge of their natural and built landscapes, while contributing to the reduction of mosquito-borne disease risk in their communities. This highlights the benefit of coupling citizen science to a virtual internship. Interns’ interest in research, and research in the earth sciences specifically, increased as a result of participating in the internship program. By leveraging citizen science data collection and reporting tools, existing data, and analysis tools, the program represented a robust, cost effective research experience conducted in a virtual environment, lowering barriers to participation and broadening access to STEM enhancement opportunities for all.